2020
DOI: 10.3329/bjmm.v14i2.57794
|View full text |Cite
|
Sign up to set email alerts
|

Serological and Molecular Epidemiology of Human Brucellosis in Mymensingh region Bangladesh

Abstract: Brucellosis is a major Bacterial Zoonotic disease worldwide. More than 500,000 new cases are reported globally every year with the annual incidence rates varying widely from <2 to >500 per 1000,000 population among different region of the world. This cross sectional descriptive study was carried out in the department of microbiology, Mymensingh medical college, Mymensingh, Bangladesh from 1st January to 31 December 2017, on total 600 patients of PUO with or without occupational exposure. Blood was taken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Kaur et al reported in their study that the prevalence of human brucellosis by ELISA was 6% [ 13 ]. In contrast to other studies, Sharma et al reported overall seroprevalence of brucellosis at 4.96% from Jammu district in North India [ 22 ], Barua et al reported 17.64% B. melitensis [ 23 ], Rasheduzzaman et al reported Brucella positivity 5.45% by PCR and 3.64% with RT-PCR [ 24 ].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Kaur et al reported in their study that the prevalence of human brucellosis by ELISA was 6% [ 13 ]. In contrast to other studies, Sharma et al reported overall seroprevalence of brucellosis at 4.96% from Jammu district in North India [ 22 ], Barua et al reported 17.64% B. melitensis [ 23 ], Rasheduzzaman et al reported Brucella positivity 5.45% by PCR and 3.64% with RT-PCR [ 24 ].…”
Section: Discussionmentioning
confidence: 96%
“…In contrast to other studies, Sharma et al reported overall seroprevalence of brucellosis at 4.96% from Jammu district in North India[22], Barua et al reported 17.64% B. melitensis[23], Rasheduzzaman et al reported Brucella positivity 5.45% by PCR and 3.64% with RT-PCR[24].Brucellosis is endemic in India[23]. Several studies have reported the prevalence of animal brucellosis in India.Saeed et al conducted a study in which village-wise variations were found for animal brucellosis in 61.5% of goats, 75% of sheep, 87.5% of buffaloes, and 89% of cattle by Rose Bengal Plate Test (RBPT) and PCR from central Punjab and Pakistan [25].…”
mentioning
confidence: 91%